2011
DOI: 10.2147/opth.s15971
|View full text |Cite
|
Sign up to set email alerts
|

Novel ocular antihypertensive compounds in clinical trials

Abstract: Introduction:Glaucoma is a multifactorial disease characterized by progressive optic nerve injury and visual field defects. Elevated intraocular pressure (IOP) is the most widely recognized risk factor for the onset and progression of open-angle glaucoma, and IOP-lowering medications comprise the primary treatment strategy. IOP elevation in glaucoma is associated with diminished or obstructed aqueous humor outflow. Pharmacotherapy reduces IOP by suppressing aqueous inflow and/or increasing aqueous outflow.Purp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
113
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(120 citation statements)
references
References 80 publications
1
113
0
3
Order By: Relevance
“…However, the company discontinued an early phase II clinical trial reporting only a small reduction of IOP without a clear dose-response relationship. 117 In the Marfan mouse model, selective inhibition of AT1 with losartan more effectively prevented thickening of the aortic wall than did inhibition of both AT1 and AT2 with ACE inhibitors (Fig. 3), even though ACE inhibitors were more effective in reducing TGFb signaling.…”
Section: Microfibril Defects and Chronic Over-activation Of Tgfb Signmentioning
confidence: 97%
“…However, the company discontinued an early phase II clinical trial reporting only a small reduction of IOP without a clear dose-response relationship. 117 In the Marfan mouse model, selective inhibition of AT1 with losartan more effectively prevented thickening of the aortic wall than did inhibition of both AT1 and AT2 with ACE inhibitors (Fig. 3), even though ACE inhibitors were more effective in reducing TGFb signaling.…”
Section: Microfibril Defects and Chronic Over-activation Of Tgfb Signmentioning
confidence: 97%
“…Receptor activation has also been shown to induce the secretion of MMPs, particularly MMP-2, probably the cause of reduced outflow resistance [167,168]. Increases in facility were negated by the addition of an MMP inhibitor, implicating ECM remodeling along with cell volume shrinkage as mediators of outflow enhancement [169,170].…”
Section: New Classes Of Drugmentioning
confidence: 99%
“…Phase 2 clinical studies demonstrated the efficacy and safety in subjects with open angle glaucoma and ocular hypertension [21]. Intracanalicular inserts loaded with travoprost is being developed by ocular therapeutix for the treatment of glaucoma and ocular hypertension.…”
Section: Literature Review Novel Drug Delivery Systemsmentioning
confidence: 99%